Analysis of Students’ Scientific Reasoning Profiles Using the Lawson’s Classroom Test of Scientific Reasoning - Hebron Pardede; Mariana Surbakti; Bajongga Silaban (Department of Physics Education, Universitas Mataram, 2026)
This study investigates the scientific reasoning profiles of physics education students using Lawson’s Classroom Test of Scientific Reasoning (LCTSR). A descriptive quantitative design was employed with 50 undergraduate students from the Physics Education Study Program at Universitas HKBP Nommensen, Indonesia. The LCTSR instrument consists of 30 paired multiple-choice items assessing six dimensions of scientific reasoning: conservation reasoning, proportional reasoning, control of variables, probabilistic reasoning, correlational reasoning, and hypothetico-deductive reasoning. The results show that the mean LCTSR score was 12.4 out of 30, indicating that most students were at the transitional reasoning level. Specifically, 30% of students were classified as concrete reasoners, 56% as transitional reasoners, and only 14% as formal reasoners. Among the six reasoning aspects, conservation reasoning demonstrated the highest achievement (77.5%), whereas hypothetico-deductive reasoning was the weakest (16.7%). The findings indicate substantial difficulties in abstract reasoning processes. These results highlight the need for explicit instructional strategies to promote higher-order scientific reasoning in physics education programs.